Tracking and Formation Control of Leader-Follower Cooperative Mobile Robots Based on Trilateration Data - Ningrum, Endah Suryawati; Hakkun, Rizky Yuniar; Alasiry, Ali Husein (Politeknik Elektronika Negeri Surabaya (PENS), 2015)
This research deals with formation control of swarm robot based on changing of robot’s relative positional data. A follow the leader movement with simple triangle formation case is applied with three robots; a leader with two followers. Trilateration method is used as a method of determining the position of the leader robot from the follower robots using the distance to the reference point (local positioning). Follower robots are designed to follow every movement of the leader on a formation position. The controller is designed to maintain the formation position of the follower robots relatively to the leader. As a uniqueness, a relative positional control method by using bearing angle and distance error is proposed instead of the common Cartesian positional error control. From the experiment which conducted in maximum distance between the robots,it was obtained a maximum error approximately 56%. The follower robots are able to follow any changes in motion of the robot leader with average distance error of 36%.Keywords: Cooperative mobile robot, formation control, trilateration, follow the leader